FUNCTIONAL ANATOMY AND MODERN DIAGNOSTICS OF STATE OF TEMPOROMANDIBULAR JOINT - R. Palivoda; V. Malanchuk; O. Volovar; O. Kovalchuk (Bogomolets National Medical University, 2015)
Summary. Temporomandibular joint (TMJ) is one of the complex functional structure of human body. Study of functional anatomy of maxillofacial area (MFA) was started from ancient times. Today due to modern equipment and digital stomatology, functional method of diagnostics of TMJ was researched. Goal of this study is investigate level of necessity of complex functional approaches in patients with TMJ diseases. We described clinical case, made complex functional diagnostics:              joint vibration analysis, electromyography, digital axiography, state of connective tissue, received good results. It was important to have correct plan of treatment including individual human features and anatomy of MFA (bone, chewing muscles, teeth).